Commensurability effects in magnetic properties of superconducting Nb thin films with periodic submicrometric pores - Chiliotte, Claudio Ezequiel (2009)
Pinning properties in 100 nm thick continuous and porous superconducting Nb films are examined by ac susceptibility and dc magnetization measurements. The Nb film was deposited on a smooth Si substrate, while the porous film, NbP, was deposited on an anodized Al oxide substrate. Pores or "antidots" 40 nm in diameter, 100 nm apart, form a triangular array. The porous film presents commensurate or matching field effects for applied magnetic fields where the magnetic flux threading each unit cell is an integer number of the flux quantum, where ac shielding capability and dc diamagnetic magnetization show an abrupt increase. The response to ac fields as a function of temperature and dc field provided a way to determine that NbP sample has higher pinning than the continuous one, and that TC suppression due to fluxoid quantization is not relevant for the investigated temperature range. © 2009 Elsevier B.V. All rights reserved.